1999
DOI: 10.1038/sj.bjp.0702385
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel polymorphisms within the promoter region of the human β2 adrenergic receptor gene

Abstract: By screening the 1470 bp 5′ to the start codon of the human β2 adrenergic receptor gene, we have identified a total of eight polymorphisms (−20 T→C, −47 T→C, −367 T→C, −468 C→G, −654 G→A, −1023 G→A, −1343 A→G and −1429 T→A c.f. β2 adrenergic receptor start codon). Transient transfection of 5′ flanking deletion luciferase reporter constructs demonstrated the majority of activity of the human β2 adrenergic gene 5′ flanking region to be present within a 549 bp fragment immediately upstream from the start codon. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
73
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 10 publications
1
73
1
1
Order By: Relevance
“…Polymorphisms within the promoter region of ADRB2, especially those at -47T>C (BUP-cys to BUP-arg) and -367T>C, have been associated with differences in β 2 -adrenoceptor expression in transfected cells [11][12][13][14][15]. By contrast, a study using lymphocytes isolated from asthmatics demonstrated that there was no association between the polymorphism at -47 and β 2 -adrenoceptor expression [17].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Polymorphisms within the promoter region of ADRB2, especially those at -47T>C (BUP-cys to BUP-arg) and -367T>C, have been associated with differences in β 2 -adrenoceptor expression in transfected cells [11][12][13][14][15]. By contrast, a study using lymphocytes isolated from asthmatics demonstrated that there was no association between the polymorphism at -47 and β 2 -adrenoceptor expression [17].…”
Section: Discussionmentioning
confidence: 99%
“…3). Position -367 within the promoter region of ADRB2 has also been linked to influencing receptor expression [12,15]. However, in human lung this position had no influence on β 2 -adrenoceptor expression ( Table 4).…”
Section: Article In Pressmentioning
confidence: 99%
See 3 more Smart Citations